Aplikasi Lamikro: Solusi Rendahnya Tingkat Pelaporan Keuangan UMKM di Kabupaten Dompu - RAMADHAN, MUH. SYAHRU; ADHIM, CHAIRUL; ISKANDAR, RIZKIANA; ROSTINA; ANNISA (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2025)
Purpose – The purpose of this community service is to improve the ability of MSME actors in terms of digital financial recording using the LAMIKRO application and provide an understanding of digital marketing and how to manage business registration numbers (NIB) for MSMEs. Design/methodology/approach – The methods used in this community service program consist of the socialization stage, training stage, and mentoring stage. The number of MSMEs involved in this program is 27 MSMEs in Dompu Regency. Findings – The results of this training showed quite satisfactory results and were in accordance with the expected targets. Partners felt significant benefits, namely having the ability to record financial transactions with the LAMIKRO application. In addition, partners understand the process of marketing products digitally through social media and can apply for a business registration number (NIB) online easily. Originality/value – This community service program has never been carried out on program partners, so it will focus on two main areas, namely education and information technology and the field of MSME business management.